ANALISIS SISTEM PENGENDALIAN INTERN DAN PEMANFAATAN IT GOVERNANCE TERHADAP KEANDALAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN MINAHASA TENGGARA MENGGUNAKAN FRAMEWORK COBIT (Control Objectives For Information And Related Technology) - Ole, Halens Ryanlie; Nangoi, Grace; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
The purpose of this study was to assess the internal control system in a number of â€œSKPDâ€ in Southeast Minahasa Regency and check also the utilization of IT Governance at the â€œSKPDâ€. This study uses the COBIT framework to analyze the system of internal control and utilization of IT Governance in sectors in Southeast Minahasa Regency. The method used in this research using descriptive method by distributing questionnaires purposive sampling to target treasurer, operator, or financial administration officials are determined randomly. Obtained data is then processed and dideskriptifkan by researchers thus a detailed explanation of the study. The results showed that the Financial Statements To improve the reliability of the Local Government needed improvements in terms of control and monitoring activities. Meanwhile, IT Governance are not yet standardized, but have had the procedure. The most mature component is information architecture while most adults are communication objectives and management direction.